2023
DOI: 10.2337/dc22-1018
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Factors and All-Cause Mortality in Individuals With Type 2 Diabetes: A Systematic Review and Meta-analysis of Prospective Observational Studies

Abstract: BACKGROUND Type 2 diabetes is a major health concern associated with mortality. Diet may influence the progression of diabetes; however, systematic reviews are lacking. PURPOSE This study systematically summarized the evidence on diet and all-cause mortality in individuals with type 2 diabetes. DATA SOURCES PubMed and Web of Science were searched until June 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…Recently, Barbaresko et al 70 systematically summarized the evidence on diet and all-cause mortality in individuals with T2DM, and from 107 studies, these authors concluded that higher intake of fish, whole grain, fiber, and omega-3 polyunsaturated FAs was inversely associated with all-cause mortality in individuals with T2DM. However, they also highlighted that there is limited evidence for other dietary factors, and thus, more research is needed.…”
Section: Gaps and Perspectivesmentioning
confidence: 99%
“…Recently, Barbaresko et al 70 systematically summarized the evidence on diet and all-cause mortality in individuals with T2DM, and from 107 studies, these authors concluded that higher intake of fish, whole grain, fiber, and omega-3 polyunsaturated FAs was inversely associated with all-cause mortality in individuals with T2DM. However, they also highlighted that there is limited evidence for other dietary factors, and thus, more research is needed.…”
Section: Gaps and Perspectivesmentioning
confidence: 99%